2017
DOI: 10.1159/000477460
|View full text |Cite|
|
Sign up to set email alerts
|

Second- to Third-Trimester Longitudinal Growth Assessment for the Prediction of Largeness for Gestational Age and Macrosomia in an Unselected Population

Abstract: Background: Prenatal detection of excessive growth remains inaccurate. Most strategies rely on a single cross-sectional evaluation of fetal size during the third trimester. Objectives: To compare second- to third-trimester longitudinal growth assessment with cross-sectional evaluation at the third trimester in the prediction of largeness for gestational age (LGA) and macrosomia. Methods: A cohort of 2,696 unselected singleton pregnancies scanned at 21 ± 2 and 32 ± 2 weeks was created. Abdominal circumference (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…Our finding that the addition of growth velocity between 32 and 36 weeks' gestation did not improve the prediction of a LGA neonate provided by EFW at 36 weeks alone is consistent with the results of a study that examined 3440 pregnancies and reported that serial fetal biometry did not improve the prediction of a LGA neonate provided by the last EFW before delivery alone, and of another study that examined 2696 pregnancies and reported that AC growth velocity between 22 and 32 weeks did not improve the prediction of a LGA neonate provided by AC at 32 weeks. Similarly, in previous studies, we reported that growth velocity between 22 and 36 weeks and between 32 and 36 weeks did not improve the predictive performance for small‐for‐gestational‐age (SGA) neonates provided by EFW at 36 weeks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that the addition of growth velocity between 32 and 36 weeks' gestation did not improve the prediction of a LGA neonate provided by EFW at 36 weeks alone is consistent with the results of a study that examined 3440 pregnancies and reported that serial fetal biometry did not improve the prediction of a LGA neonate provided by the last EFW before delivery alone, and of another study that examined 2696 pregnancies and reported that AC growth velocity between 22 and 32 weeks did not improve the prediction of a LGA neonate provided by AC at 32 weeks. Similarly, in previous studies, we reported that growth velocity between 22 and 36 weeks and between 32 and 36 weeks did not improve the predictive performance for small‐for‐gestational‐age (SGA) neonates provided by EFW at 36 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…Fourth, on the issue of timing of the third-trimester scan, there is some evidence that the predictive performance of a scan for LGA neonates at 36 weeks' gestation may be superior to that at 32 weeks 14,15 . Fifth, there is uncertainty as to the additive value for prediction of a LGA neonate of fetal growth velocity to the performance of EFW during the late third trimester [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Our results are not in concordance with Blue, who observed that after the 24 th week of gestation AC measurement has no advantage in the LGA risk assessment in fetuses with estimated overgrowth [14]. Caradeux has not confirmed the effectiveness of longitudinal growth assessment as a better method to detect excessive growth compared to standard biometric measurements [15]. In our opinion although fetal weight estimation is still imperfect there is no better way, as longitudinal observations to diagnose hypertrophy among fetuses.…”
Section: Discussioncontrasting
confidence: 96%
“…These findings are in line with a recent definition of late FGR by 56 participating experts 63 , which considered a decline of more than two quartiles in a growth chart to be a criterion for late FGR. Previous studies have demonstrated that a decline in fetal growth velocity is a major determinant of adverse perinatal outcome both in SGA 31,34,53 and appropriately grown 64–67 fetuses. According to Chatzakis et al 67 ,.…”
Section: Discussionmentioning
confidence: 99%